Simple estimate of creatinine clearance from plasma creatinine in neonates. Issue 4 (April 1982) - Zacchello, G; Bondio, M; Saia, O S; Largaiolli, G; Vedaldi, R; Rubaltelli, F F
Abstract : Thirteen newborn infants, 8 preterm and 5 term, with either mild or serious neonatal asphyxia were studied. From the first 24 hours of life to day 13, glomerular filtration rate (GFR) estimated by creatinine clearance was compared with the values obtained using Schwartz's formula: GFR (ml/min per 1.73 m2) = 0.55 x length (cm)/plasma creatinine (mg/100 ml). Both in term and preterm infants, values of formula-calculated creatinine clearance were slightly higher than values obtained by the classical method; nevertheless the data show significant correlations, respectively r = 0.867 and r = 0.795 (P less than 0.001). This formula provides an adequate estimation of neonatal creatinine clearance (a marker for GFR) directly from plasma creatinine provided that body length is taken into consideration. The necessity for urine collection and the associated problems are thus obviated. The simplicity of Schwartz's formula permits easy monitoring of renal function, especially in neonatal asphyxia in which the risk of developing renal failure is great.